POLA KONSUMSI DAN SIKAP MAHASISWA UNIVERSITAS LAMPUNG TERHADAP KOPI ROBUSTA - Nur Nazariah; Yaktiworo Indriani; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purpose of this study was to determine the attitudes and consumption patterns of University of Lampung (Unila) students towards Robusta coffee.  This research was a survey carried out in the University of Lampung.  The total sample was 90 students who consumed robusta coffee.  The research data were collected in March to May 2019 by interviews using questionnaires, google form, and whatsapp.  Data were analyzed quantitatively and qualitatively.  The results showed that student respondents consumed robusta coffee once a day.  Most consumers chose the coffee attributes that were most important, namely the expiration date and taste of Robusta coffee.  The results of the multiatribute analysis of Fishbein on consumer attitudes indicated that the attitude score of taste gets the highest value of 18.50, followed by the halal label attribute of 18.40.  The multiatribute attitude score (Ao) of robusta coffee was 162.30.  It means that robusta coffee has a positive value and is prefered by student consumers.Key words: attitude, Fishbein multiatribute, consumption patterns, robusta coffee